Does Divorce Make People Happy? - Donna Davis (EDIS)
“The marriage and divorce trends of the “modern” American family have been studied for decades. In an attempt to further understand the outcomes of divorce, a team of family scholars headed by University of Chicago sociologist Linda Waite studied whether unhappily married adults who divorced were any happier than unhappily married people who stayed married.” This 2-page fact sheet was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, September 2012.